Transfermarkt Estimates of Player Values in Top-Division Croatian Football - Alajbeg, Denis (Oeconomica Jadertina, 2023)
For many years now, the Transfermarkt website has been the most popular global reference point for market value estimates of football players. Since most top-flight Croatian football clubs lean heavily on financing through the sale of player registrations, it is useful to know by how much valuation estimates of that portal differ from actual transfer fees, as well as how many players are transferred with financial compensation involved. Analyzing Croatian first league clubs over a period of ten playing seasons, this paper found that no transfer fees were recorded in the majority of outgoing transfers (at least in 55% of cases, but probably up to 85%). Consequently, the total transfer value is up to 40% lower than total market value estimates of these players on Transfermarkt at the time of their departure from clubs. However, when considering only transfers with paid compensation, market value estimates from Transfermarkt and transfer fees almost overlap, with a difference of only 1,5%. A strong and significant statistical relationship between market value estimates and transfer fees has been confirmed, but only for outgoing transfers where compensation was actually paid. The probability of a paid transfer increases with increasing market value - especially above one million euros per player - and an increased market value also enhances the accuracy of future transfer fees assessments. Since more successful Croatian clubs have more players with higher market values in their squad, Transfermarkt’s estimates are more accurate for them than for less successful domestic clubs.